Investment in R&D as a Trigger for Accelerated Development of the Digital Economy Ecosystem: A Comparative Analysis of OECD Countries - Malika A. SADUEVA; Olga Y. KUZMINA; Elena E. KUKINA; Anna S. SHURUPOVA; Evgeniya K. KARPUNINA (Communications of International Proceedings, 2020)
The purpose of the research is to reveal the infrastructure for generating innovations based on R&D as a structural element of the digital economy ecosystem, which provides a trigger effect of accelerated digital development of the national economy, as well as to develop a mechanism for making management decisions about investing in R&D using a trigger. The authors revealed the configuration of the digital economy ecosystem based on innovation generation subsystem. The authors analyzed the dynamics of investment in R&D in the OECD countries-leaders and outsiders in the IMD Global digital competitiveness rating 2019, compared their structure, and evaluated the effectiveness in the form of the number of registered patents, changes in labor productivity, as well as indicators of "technology", "knowledge", and "future readiness". The authors suggested using the trigger mechanism in the process of making management decisions about investing in R&D, and also justified the criterion for differentiating public policy.
Keywords: the digital economy; R&D investments; the trigger; the digital economy ecosystem; generating innovation